Social Media Marketing Activities, Brand Trust, and Brand Loyalty in The Insurance Industry: Evidence from Zurich Indonesia - Alam, Rindang Nur; Jahroh, Siti; Shalihati, Fithriyyah (Business Review and Case Studies, 2026)
Background: The rapid growth of social media in Indonesia, with 143 million active users, has made it the primary marketing channel for 63% of Indonesian insurance companies. Despite high digital engagement, the mechanisms linking social media marketing activities (SMMA) to brand loyalty in the insurance sector remain empirically underexplored.Purpose: This study examines how SMMA affects brand loyalty directly and indirectly through brand trust among customers of Zurich Indonesia.Design/Methodology/Approach: A quantitative cross-sectional survey of 200 active Instagram followers of @zurichid was analysed using SEM-PLS with a two-stage approach in SmartPLS 4.0.Findings/Result: SMMA significantly affects brand loyalty (β=0.247, t=3.181, p=0.001) and brand trust (β=0.469, t=5.406, p